ANALISIS PRODUKSI BIOGAS SEBAGAI ENERGI ALTERNATIF PADA KOMPOR BIOGAS MENGGUNAKAN CAMPURAN KOTORAN SAPI DAN AMPAS TAHU - Paulus Vilino Hasahatan Sinaga; Doddy Suanggana; Hadhimas Dwi Haryono (P3M Politeknik Negeri Indramayu, 2022)
Biogas decomposes organic waste by bacteria through an anaerobic fermentation process that produces manageable methane gas. The purpose of this study was to determine the temperature, pressure, mass and flame duration of biogas produced from a mixture of cow dung and tofu waste liquid waste using a batch type digester. The digester uses a volume capacity of 30 liters with a volume of stuffing raw material as much as of the volume of the digester. This study uses three variations of the volume ratio of the mixture of cow dung and tofu waste liquid waste, namely S1 (50%: 50%), S2 (70%: 30%), and S3 (90%: 10%) with the addition of 2.5 liters of water for each variation. Data collection was carried out for 30 days at 11.00 WITA and 17.00 WITA. Based on the results of the study, it is known that the mixed variation of 50%: 50% is the best variation compared to the variations of 70%: 30%, and 90%: 10%. The results of the daily average environmental temperature variation of the S1 mixture are 30.19°C, and the average substrate temperature are 27.06°C. The average daily yield of biogas pressure are 0.039 bar with a total mass of biogas are 57.8 grams. Based on the measurement results of biogas flame duration comparasion with LPG on the total mass of biogas with the variation of the S1 mixture, it is obtained that biogas flame duration are 4.38 minutes while the combustion of LPG gas with the same total mass are 49 seconds.